Assessment of laminar flame velocity of producer gas from biomass gasification using the Bunsen burner method. (14th April 2020) - Andrade, Rubenildo Vieira; Cortabarria Castañeda, Laura Andrea; Yepes Maya, Diego Mauricio; Pedroso Cesar Corrêa Junior, Paulo Sergio; Mello e Pinto, Luis Roberto; Silva Lora, Electo Eduardo; Vilas Bôas de Sales Oliveira, Cristina Aparecida; Pinto, Bruno Augusto
Abstract: Producer gas is a renewable fuel obtained from gasification processes. This fuel may be burned directly in furnaces to supply thermal demands, or used to run internal combustion engines or gas turbines. The characteristics of producer gas have been studied by various authors, however, most studies generally use mixtures of synthetic gases to represent Producer Gas. The main goal of this study is to evaluate the laminar flame velocity of Producer Gas obtained from gasifying eucalyptus wood in a two-stage downdraft gasifier using the Bunsen burner method and the Schlieren image visualization technique to register the profile of the flame. The Producer Gas volume fractions that were used in the tests were 20%, 16%, and 1.8% for CO, H2, and CH4, respectively. This resulted in a 4.9 MJ/Nm³ lower heating value. The registered laminar flame velocity at the stoichiometric point under optimal conditions was 0.33 m/s. The tests were carried out at standard atmospheric pressure and atmospheric temperature. The results were compared to studies of other authors, and this study shows that fractions of Hydrogen (H2 ) and Carbon Monoxide (CO) in the Producer Gas result in increased laminar flame velocities, while fractions Nitrogen (N2 ) and Carbon Dioxide (CO2 ) result in reduced flame velocities. Highlights: The syngas laminar flame velocity was determinate from Bunsen Burner methodology. It was observed that the fraction of hydrogen in producer gas influence the laminar flame velocity. Schlieren technique to register the flame shape was applied with success and present good results. The gasifier system was used to supply producer gas with adequate conditions for the tests carried out. The major value obtained to flame velocity was 0.33 m/s.